Analisis Pemahaman Konsep Matematis Peserta Didik Sekolah Dasar: Dampak Model Project Based Learning Model - Komarudin, Komarudin; Puspita, Laila; Suherman, Suherman; Fauziyyah, Isya (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The study aims to determine the influence of the PjBL model in understanding the mathematical concepts of elementary school students. The study involved two classes, one class as an experimental class given the PjBL model treatment and one class as an untreated control class with the PjBL learning model. The design of this study uses Posttest-Only Control Designe. Data collection using test techniques. Test techniques are conducted to obtain data about understanding the mathematical concept of students. Data analysis is done using Paired Sample . Based on data analysis and discussion it is known that to 1.71387. In accordance with the interpretation of , the hypothesis was received if the > , with the result 4.13 > 1.71387 then rejected. It can be concluded that understanding the concept of learners that are taught with the PjBL model is higher compared to the average understanding of students' concepts that do not use the PjBL model, so it can be concluded that there are Positive influence on the use of PjBL model to understand the concept of students of elementary school in Pesis district.